2006
DOI: 10.1203/01.pdr.0000242304.64309.6c
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric Jet Doppler Waveform and Bladder Wall Thickness in Children With Nocturnal Enuresis

Abstract: In this article, the authors propose a non-invasive method to evaluate children with enuresis by correlating findings of color Doppler ultrasound of ureteric jet and bladder wall thickness. The authors compared the ultrasound findings in a group ABSTRACT:To test the hypothesis that the presence of nocturnal enuresis is related to increased frequency of immature vesicoureteric function, which is further associated with detrusor overactivity, we compared the incidence of immature monophasic ureteric jet in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…The incidence of immature monophasic jet was significantly greater in enuretic children (19.2% in both sides) than in normal children (6.4% on the right side and 8.3% on the left side). Furthermore, the immature waveform was more commonly seen in the enuretic group with a markedly thickened bladder wall and multiple urodynamic abnormalities [5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of immature monophasic jet was significantly greater in enuretic children (19.2% in both sides) than in normal children (6.4% on the right side and 8.3% on the left side). Furthermore, the immature waveform was more commonly seen in the enuretic group with a markedly thickened bladder wall and multiple urodynamic abnormalities [5]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the association of the monophasic jet waveform with VUR and UTI might partially explain why pregnant women with a higher incidence of the monophasic jet pattern are also more prone to VUR and UTI [4]. A higher incidence of the immature jet pattern is also found in children with nocturnal enuresis [5]. This suggests that there is a lower level of maturity of the VUJ in a proportion of enuretic children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we postulated that dilated RP might associate with bladder dysfunction, which could be reflected by abnormal bladder parameters such as MaxBV, RV, and BWT quantitatively. Our previous study on enuretic children has showed that there were significant correlations between abnormal thickness of the bladder wall and multiple abnormal parameters demonstrated by urodynamic studies (10).…”
Section: Discussionmentioning
confidence: 94%
“…2010;43(1): 35-38. ner. The alterations in the function of the lower urinary tract may be divided into neurological (neurogenic bladder), most frequently resulting from spinal dysraphism and cerebral palsy; and functional, caused by disorders in children with no evidence of neurological diseases (1,2) . The relevance of early diagnosis is related to the possibility of establishing the treatment in order to…”
mentioning
confidence: 99%